IT GOVERNANCE OF SENAYAN LIBRARY MANAGEMENT SYSTEM (SLIMS) LIBRARY AND ARCHIVES DEPARTMENT OF EAST KALIMANTAN PROVINCE USING COBIT 5.0 - Ita Arfyanti; Nursobah Nursobah; Rajiansyah Rajiansyah (Jurnal Ilmiah Matrik, 2021)
The existence of an information system in the Library and Archives Department of East Kalimantan needs to be properly maintained and supervised so that the organizational system is in line with the agency's goals. One way to ensure this is to conduct an information system performance analysis. This study uses the Control Objective for Information and related Technology (COBIT) version 5.0, which is a best practice that provides activities managed by the IT organizational structure within a framework in the form of a product, to focus on execution and control that has been made from experts from the field of technology governance Information. This practice can maximize IT investment, to assess if there are errors in providing measurements made and delivering services. Therefore, in order to achieve the target, this research was carried out using the COBIT 5.0 framework in order to be able to analyze an information system performance at the Library and Archives Department of East Kalimantan. The results of this study indicate that MEA01 is at level 5 (Optimizing Process), MEA02 is at level 3 (Established Process), MEA03 is at level 2 (Managed Process). In this case the Regional Library and Archives Office of East Kalimantan to be more efficient in the use of IT requires handling of the factors that influence it so that it is maximal, the use of IT for all employees in the operation of the Senayan Library Management System (SLiMS) and also the person in charge of IT to keep pace with developments technology.